Room‐Temperature Nonvolatile Memory Based on a Single‐Phase Multiferroic Hexaferrite - Zhai, Kun; Shang, Da‐Shan; Chai, Yi‐Sheng; Li, Gang; Cai, Jian‐Wang; Shen, Bao‐Gen; Sun, Young (Advanced functional materials, 2018)
The cross‐coupling between electric polarization and magnetization in multiferroic materials provides a great potential for creating next‐generation memory devices. Current studies on magnetoelectric (ME) applications mainly focus on ferromagnetic/ferroelectric heterostructures because single‐phase multiferroics with strong magnetoelectric coupling at room temperature are still very rare. Here a type of nonvolatile memory device is presented solely based on a single‐phase multiferroic hexaferrite Sr3Co2Fe24O41 which exhibits nonlinear magnetoelectric effects at room temperature. The principle is to store binary information by employing the states (magnitude and sign) of the first‐order and the second‐order magnetoelectric coefficients (α and β), instead of using magnetization, electric polarization, and resistance. The experiments demonstrate repeatable nonvolatile switch of α and β by applying pulsed electric fields at room temperature, respectively. Such kind of memory device using single‐phase multiferroics paves a pathway toward practical applications of spin‐driven multiferroics. A nonvolatile memory with low energy consumption is achieved by using a single‐phase multiferroic materials, Sr3Co2Fe24O41, based on its nonlinear magnetoelectric effects at room temperature. Instead of using the states of magnetization, electric polarization, and resistance to store binary information, this type of nonvolatile memory employs the states (magnitude and sign) of the magnetoelectric coefficients to encode binary information.